The Characterization of Lung Cancer - Rizzo, Toni (MD Conference Express, 2012)
This article discusses the characterization of non-small cell lung cancer (NSCLC), including its histology, biology, and molecular classification, and an integrative approach to its management. Lung cancer was first characterized by Rudolf Virchow in the 1800s as a tumor in the lungs that could be diagnosed by examining a pathological sample. While this definition is still in use today, lung cancer is, in fact, the result of multiple molecular alterations underlying the phenotypic changes observed in the cells.